Impact of Social Media Influencers on Consumer Purchasing Decisions: A Case of Generation Z in Nepal - Khanal, Snehee; Pradhan, Sumit (Nepalese Journal of Economics, 2025)
This study examines the impact of social media influencers on consumer purchasing decisions: A case of generation Z in Nepal. Consumer buying behavior is the dependent variable. The selected independent variables are popularity, engagement level, information content, endorsement frequency, and relatedness. The primary source of data is used to assess the opinions of respondents regarding popularity, engagement level, information content, endorsement frequency, relatedness, and consumer buying behavior. The study is based on primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of social media influencers on consumer buying behavior. The study showed a positive impact of popularity on consumer buying behavior. It indicates that popularity of social media influencers leads to increase in consumer buying behavior. Similarly, the study showed a positive impact of engagement level on consumer buying behavior. It indicates that higher the engagement level of social media influencers, higher would be the consumer buying behavior. Likewise, the study also revealed a positive impact of information content on consumer buying behavior. It indicates that quality information content leads to increase in consumer buying behavior. Further, the study observed a positive impact of endorsement frequency on consumer buying behavior. It indicates that higher the endorsement frequency, higher would be the consumer buying behavior. In addition, the study observed a positive impact of relatedness on consumer buying behavior. It indicates that higher the desire to feel loved and connected to others, higher would be the consumer buying behavior.